Introduction to Special Issue on Inequalities and Youth Mobilities in Europe from Comparative Perspectives - Samuk Carignani, Sahizer; Kmiotek-Meier, Emilia; Nienaber, Birte; Vysotskaya, Volha (Migration Letters, 2018)
Where does youth mobility stand in the complex picture of diverse types of inequalities that affect youth and the content of their mobilities? In the light of this question, with this special issue, we look at the hindering and fostering factors in the mobility of young people, and examine different facets of mobility (social networks, transnational activities, agency, gender, household decisions) in different types of mobility (considering mobility for volunteering, vocational education and training, higher education including both credit and degree mobility, and employment). The analysis presented in the papers of this special issue will enable the identification of inequalities accompanying youth mobility at different levels. The articles in this issue reveal that when it comes to possibilities for becoming mobile, many other types of inequalities apart from the solely economic ones must be considered (Oxfam, 2016, p. 7; Hargittai and Hinnant 2008), including legal, political, social, moral inequalities (White, 2007) together with gender inequality. This special issue on “Inequalities and Youth Mobilities in Europe from Comparative Perspectives” serves the purpose of revealing how diverse types of inequalities can exist within seemingly equal societies.